2023
DOI: 10.3390/biology12030458
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Polymorphisms in Toll-like Receptors 2, 3, 4, 7, 9, miR-146a, miR-155, and miR-196a Genes on Osteoarthritis Susceptibility

Abstract: Osteoarthritis (OA) is a progressive inflammatory disease of synovial joints and a leading cause of disability among adults. Inflammation-related genes, including genes for Toll-like receptors (TLRs), are tightly controlled by several microRNAs that, in addition to their pivotal role in the epigenetic regulation of target genes, are ligands for TLR activation and downstream signaling. Thus, we evaluated the association between OA risk and genetic variants in TLR2, TLR3, TLR4, TLR7, TLR9, and microRNAs that reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
1
4
1
1
Order By: Relevance
“…This means that there are different risk populations, and miR-146a is a significant modifying factor. So, our results regarding the role of the miR-146a gene in affecting the genetic risk of PHOA are in disagreement with the study by Stefik et al 19 We believe that these authors 19 have not found significance in their analyses due to the small sample size of the study and consequently being unable to stratify results.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…This means that there are different risk populations, and miR-146a is a significant modifying factor. So, our results regarding the role of the miR-146a gene in affecting the genetic risk of PHOA are in disagreement with the study by Stefik et al 19 We believe that these authors 19 have not found significance in their analyses due to the small sample size of the study and consequently being unable to stratify results.…”
Section: Discussioncontrasting
confidence: 97%
“…Our study is the first of this type in the Croatian (Caucasian) population. Regarding the role of the miR-146a gene in affecting the genetic risk of PKOA, our results seem to be in agreement with studies by Papathanasiou et al, 17 Miranda-Duarte et al, 18 and Stefik et al, 19 and are in disagreement with studies by Liu and colleagues. 5,26 In our study with 609 patients with end-stage POA, it was investigated the association of the miR-146a SNP rs2910164 (G>C) with a predisposition to PHOA.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The intricate association observed between the rs767649 TA/AA genotype and an increased risk of RA in the multivariate analysis raises questions regarding the precise role of this genetic variant in RA pathogenesis. The miR-155 rs767649 polymorphism is known to influence key regulatory pathways within the immune system [16,17], potentially exacerbating the inflammatory responses characteristic of RA. This finding suggests a nuanced genetic landscape contributing to RA susceptibility, indicating the necessity for further investigations on the molecular mechanisms underlying the influence of this specific genotype on the complex interplay of immune dysregulations in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Однако имеется ряд публикаций, оценивающих ассоциацию данного полиморфизма с негативным и протективным влиянием в отношении ряда других нозологий. В настоящее время показана ассоциация данного полиморфизма с некоторыми аутоиммунными и онкологическими заболеваниями [25][26][27][28]. Известно, что TLR3 связывают двухцепочечную рибонуклеиновую кислоту (РНК) вирусов, бактерий, грибов и матричную РНК, выделяемую из некротизированных клеток [29].…”
Section: показана протективнаяunclassified